Intraductal pneumatic lithotripsy for salivary stones with the StoneBreaker: Preliminary experience - Koch, Michael; Mantsopoulos, Konstantinos; Schapher, Mirco; Von Scotti, Felix; Iro, Heinrich (Laryngoscope, 2016)
OBJECTIVES/HYPOTHESIS: To test the effectiveness of a newly approved pneumatic lithotripter for fragmentation of salivary stones. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: In 44 patients, 49 stones were primarily treated with direct endoscopic guidance using the StoneBreaker. Twenty-three stones were located in the parotid gland and 26 in the submandibular gland. RESULTS: Complete fragmentation was achieved combined extracorporeal in 97.7% of the stones. All of the patients became symptom free, and 97.7% were stone free. Three patients underwent lithotripsy procedures. Altogether additional treatment was necessary in five cases to achieve stone clearance. The reason for residual sialolithiasis was intraparenchymal repulsion of a residual fragment (n = 1). The glands were preserved in all cases. CONCLUSIONS: Endoscopically guided intraductal pneumatic lithotripsy using the StoneBreaker is an effective and promising procedure for the treatment of sialolithiasis. LEVEL OF EVIDENCE: 4 Laryngoscope, 126:1545-1550, 2016.
EVALuna2:33186